Pengaruh model pembelajaran terhadap kemampuan berpikir kritis siswa - Limat, Yasinta; Sri Hariani, Lilik; Mardiana F, Riril (Jurnal Riset Pendidikan Ekonomi, 2024)
The aim of this research is to determine the use of PBL methods, media, and motivation on critical thinking skills. Quantitative is the method in this research. So this research is included in cause-and-effect research (ex-post facto) because it focuses on variables that have occurred and does not require discussion about which variables will be studied. Collection of text-based test data, questionnaires and documents. 62 students in class VIII C and D were the subjects of the research. The location of this research is SMP Negeri 12 Malang. Sampling used census research techniques, so that the entire population was used as the research population. The research results provide a significant simultaneous influence between PBL, learning materials and learning encouragement on critical thinking skills and several problem-based learning (PBL) models. The media has a partially positive impact. while motivation has a negative impact on critical thinking skills.